2019
DOI: 10.1126/sciadv.aav5447
|View full text |Cite
|
Sign up to set email alerts
|

Increased glymphatic influx is correlated with high EEG delta power and low heart rate in mice under anesthesia

Abstract: The glymphatic system is responsible for brain-wide delivery of nutrients and clearance of waste via influx of cerebrospinal fluid (CSF) alongside perivascular spaces and through the brain. Glymphatic system activity increases during sleep or ketamine/xylazine (K/X) anesthesia, yet the mechanism(s) facilitating CSF influx are poorly understood. Here, we correlated influx of a CSF tracer into the brain with electroencephalogram (EEG) power, heart rate, blood pressure, and respiratory rate in wild-type mice unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
440
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(473 citation statements)
references
References 39 publications
(43 reference statements)
31
440
0
2
Order By: Relevance
“…In order to better understand the mechanism behind VNS-induced CSF penetrance, we attempted to correlate the degree of CSF penetrance with the physiological responses recorded during stimulation. The CSF influx hypothesized to occur in the glymphatic model is driven by cerebral arterial pulsation and it was recently reported that increased glymphatic influx was correlated with a reduced HR in mice under anesthesia (24,26,38). Although no direct experiments have been undertaken to assess the effect of VNS on cerebral arterial pulsation, several studies detail the systemic cardiovascular and respiratory responses of VNS (12,13).…”
Section: Vns-induced Csf Penetrance Could Not Be Directly Linked To Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the mechanism behind VNS-induced CSF penetrance, we attempted to correlate the degree of CSF penetrance with the physiological responses recorded during stimulation. The CSF influx hypothesized to occur in the glymphatic model is driven by cerebral arterial pulsation and it was recently reported that increased glymphatic influx was correlated with a reduced HR in mice under anesthesia (24,26,38). Although no direct experiments have been undertaken to assess the effect of VNS on cerebral arterial pulsation, several studies detail the systemic cardiovascular and respiratory responses of VNS (12,13).…”
Section: Vns-induced Csf Penetrance Could Not Be Directly Linked To Cmentioning
confidence: 99%
“…Thus, it has been suggested that improvement or rescue of clearance function in these pathologies may be of potential therapeutic benefit. Importantly, aspects of the brain clearance systems are sensitive to both changes in noradrenergic signaling associated with sleep/arousal states and to cerebral arterial pulsatility which is hypothesized to drive CSF penetrance into the parenchyma (18,(24)(25)(26). Given the well-known noradrenergic, cardiovascular, and respiratory effects induced by VNS, we theorized that VNS may be able to increase CSF penetrance, thereby providing a previously unknown and unexplored therapeutic mechanism of the reported beneficial outcomes of VNS (4,12,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…The demonstrated AQP4-haplotype modulation of SWE documents an association between the intensity of deep NREM sleep and the expression of the AQP4-water channel, a relationship that may be central for CSF driven brain pulsations. Given how recent preclinical evidence show that the intensity of slow waves is directly linked to glymphatic influx (10), and that the complete removal of AQP4 in mice results in brain impairments after sleep deprivation (8), this suggest an important role of AQP4-mediated clearance during sleep. The results match our initial hypothesis suggesting that in an attempt to compensate for a reduced AQP4 expression (23), AQP4 HtMi-carriers have a stronger parenchymal CSF flow and increased SWE in NREM sleep ( Figure 1A).…”
Section: Aqp4-haplotype Modulates Slow Waves In Nrem Sleepmentioning
confidence: 99%
“…Mice lacking AQP4 show a strong reduction in parenchymal CSF influx (5,6) and increased interstitial beta-amyloid depositions (7), which is ameliorated by sleep deprivation (8). Thirdly, the inward flow of CSF through AQP4 channels mainly occurs during non-rapid eye-movement (NREM) sleep (9) and in preclinical studies, glymphatic flow is known to be positively correlated with slow wave production (10).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experimental studies and computer simulations have demonstrated that not only SWA reflects experience-dependent changes in regional synaptic density/strength, but also have indicated that slow waves may play a direct role in cellular and systems restoration and in the consolidation of newly acquired memories (Tononi and Cirelli, 2014). Recent evidence also suggested a possible implication of sleep slow waves in the clearance of neurotoxic metabolic products that accumulate during wakefulness (Xie et al, 2013;Hablitz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%